Triglyceride-Glucose Index Correlate With Telomere Length in Healthy Adults From the National Health and Nutrition Examination Survey - Hu, Lihua; Zhang, Qiaojian; Bai, Yi; Hu, Guiping; Li, Jianping (Frontiers in Endocrinology, 2022)
Aim: The present investigation was designed to test the association between leukocyte telomere length (LTL) and two simple markers of insulin resistance, i.e. homeostatic model assessment of insulin resistance (HOMA-IR) and triglyceride-glucose (TyG) index in U.S. adults without metabolic diseases. Methods: A total of 6,489 U.S. adults without diabetes from NHANES 1999–2002 were analyzed. TyG index was calculated as ln [fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. HOMA-Index was calculated as fasting plasma glucose (mmol/L) × fasting serum insulin (mU/mL)/22.5. LTL was obtained using the quantitative polymerase chain reaction method. Multivariate linear regression analysis was assessed to evaluate the association of TyG index HOMA-IR with LTL. We further conducted a generalized additive model (GAM) and a fitted smoothing curve with penalized spline method. Results: It was found that the mean LTL was 5796.1 bp in the measured healthy adults. Overall, TyG-Index was significantly associated with LTL, while HOMA-IR was not. Compared with participants in tertile 1 of TyG index, the β (95% CI) for those in the second (8.27 to 8.77) and third (≥ 8.77) were -4.31 (95% CI: -48.12~39.49) and -95.98 (95% CI: -145.08~-46.89), respectively. Subjects with TyG index ≥ 8.77 had statistically significant shorter LTL (β = -93.33, 95%CI: -134.33~-52.32), compared with TyG index < 8.77. We further explored a dose-response relation between TyG index by a decile approach [≤ 7.81 (reference), 7.81-8.04, 8.04-8.21, 8.21-8.37, 8.37-8.52, 8.52-8.68, 8.68-8.83, 8.83-9.03, 9.03-9.33, and >9.33] and LTL. 5 subgroups (TyG index 7.81-8.04, 8.04-8.21, 8.21-8.37, 8.37-8.52 and 8.52-8.68) did not show significant effect on LTL; while there was a significantly shorter LTL for participants with TyG index > 8.68, supporting a threshold effect of TyG index on LTL. Conclusions: The results suggested that higher TyG index (> 8.68) was closely related to shorter LTL and TyG index was better associated with LTL than HOMA-IR.